Catechol- and phenolic hydroxyl-functionalized partially bio-based (Co) poly(ether sulfone)s with multifarious applicability - Wale, Apparav K.; Jagtap, Ashish S.; Pandey, Priyanshi R.; Dastager, Syed G.; Shelke, Manjusha V.; Ambade, Ashootosh V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2024)
A largely bio-based new bisphenol, namely, 4,4 `-((3,4-dimethoxyphenyl)methylene)-bis(2-methoxyphenol) (DMBM) was synthesized by the reaction of veratraldehyde with guaiacol. DMBM and varying compositions of DMBM and bisphenol A were polycondensed with bis(4-fluorophenyl) sulfone to afford reasonably high molecular weight film-forming (co)poly(ether sulfone)s possessing built-in methoxyl groups. T10 and Tg values of (co)poly(ether sulfone)s were in the range 382-478 degrees C and 171-187 degrees C, respectively indicating their good thermal stability and the values decreased with increase in mol % incorporation of DMBM. The methoxyl groups present in (co)poly (ether sulfone)s were quantitatively de-blocked resulting in the formation of corresponding polymers possessing pendant catechol moieties and free phenolic hydroxyl groups. By virtue of the presence of these functional moieties, (co)poly(ether sulfone)s are amenable for post-polymerization modifications, and exhibited properties such as antimicrobial (23 mm against Staphylococcus aureus and 18 mm against Escherichia coli)), antioxidant (72 % scavenger of free radicals), adhesive (2.24 MPa lap shear strength) and usefulness as redox-active agent in zinc-ion batteries. These data underscore the promise of DMBM as a versatile monomer of wider utility for the synthesis of functional (co)poly(ether sulfone)s capable of expanding their applicability beyond the conventional ones.
Keywords: (Co)poly(ether sulfone)s; adhesive; Antimicrobial; Antioxidant; bio-based; bisphenol; Zinc-ion batteries

Stimulant immobilized bioactive film of functionalized egg albumin blend for wound healing - Gautam, Tripurari Rao; Patel, Pratikshkumar R.; Singam, Amarnath R.; Jagtap, Ashish S.; Desai, Prasad; Gundloori, Rathna V. N.; Pawar, Anil; Dastager, Syed G. (International Journal of Pharmaceutics, 2025)
Wound healing materials with advanced properties that facilitates higher collagen deposition, improved angiogenesis and quick tissue regeneration are crucial for clinical wound management. To meet the requirement, for the first time, our studies focus on engineering bio-originated natural materials, which are tested in combination with the active agents, ascorbic acid (AA), a stimulant and metronidazole (Mtz), an anti-microbial drug. Accordingly, a dual drug (AA, and Mtz) loaded film of functionalized egg albumin (FEA)-poly(vinyl alcohol) (PVA) was fabricated following the solution casting method. The film was characterized for its morphology and physicochemical properties using various analytical tools. The potential of the film as a wound healing material was evaluated, by in vitro drug release, degradation, cell viability, antimicrobial studies, in vivo wound healing, and histopathological analyses. In vitro degradation studies confirmed their degradability in enzymatic and soil burial conditions. Cytotoxicity studies demonstrated their non-toxicity, and the antimicrobial investigations showcased that the material was antibacterial. On the 14th day, the wound closure percentage of the wound induced control group, GI (without treatment) was notably higher at 95 % compared to the test formulation group, GV [FEA-PVA (30/70 w/w) loaded with Mtz and AA (10 % w/w of the total polymer weight), respectively], which exhibited a wound closure of 83 %. Furthermore, the histopathological examinations revealed that the inner wound healing in GV was comparatively better than in GI in terms of angiogenesis, epidermal remodeling, higher collagen deposition, coherency, and tissue regeneration. Consequently, the formulated film can be deemed a suitable wound dressing material.
Keywords: collagen; Dual drug release; Functionalized egg albumin; Polymer blend films; Stimulant; wound Healing